PATIENCE AS A RELIGIOUS COPING MECHANISM IN THE LEARNING PROCESS AMONG MUSLIM STUDENTS IN HIGHER EDUCATION - Ramdani, Zulmi; Mardhiana, Radin; Busro, Busro (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
A few studies have identified patience as an important part of facing problems in the learning process among Muslim students. This research aims to acquire a comprehensive understanding of the position of patience as part of a person's religious coping mechanism in promoting the academic resilience of Muslim students during the learning process in higher education in Indonesia. This study employs a systematic literature study method used in this research involving a set of reference databases such as Google Scholar, Science Direct, Sage Publications, and Research Gate, using the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) as a tool of analysis. It finds that patience is identified as part of a positive religious coping mechanism. Some factors influencing such coping mechanisms include religious rules, a person's spiritual level, a positive external environment and existing religious education. This study underscores the critical role of patience in empowering students to withstand various academic pressures in higher education.